The usage of EM in Australia - Pathinayake, Athula (Deakin University, 2018)
The raw data of cases wherein electronic monitoring or GPS monitoring has been considered. It serves to illustrate the current state of EM use by the judicial system, highlight problems, and foster theory development.
Keywords: electronic monitoring; parole; prison; drug offenders; sex offenders; sentencing; original courts; appellate courts; Australia